Enhancing Work Culture and Organizational Behavior at Kumau Laundry MSME in Lubuk Begalung, Padang - Mahelda, Selvia; Ananda, Dea; Pratiwi, Oktrisa; Ardila, Vira; Nila Sari, Vivi (LPPM Universitas Jambi, 2024)
This community engagement initiative was designed to enhance organizational behavior and foster a productive work culture within Kumau Laundry, a household-scale MSME (Micro, Small, and Medium Enterprises) located in Lubuk Begalung, Padang. A participatory approach was employed through capacity-building workshops, the co-creation of shared organizational values, and the facilitation of internal communication mechanisms. Data were gathered through participatory observation, in-depth interviews, and focused group discussions. The outcomes reveal notable improvements in internal communication effectiveness, the consolidation of a collaborative work culture, better discipline management practices, and enhanced customer service quality. The findings suggest that modest, behavior-focused interventions can yield significant positive impacts on the organizational dynamics of household-scale MSMEs. The practical implications underscore the importance of incorporating soft skills development into MSME empowerment models, beyond the conventional focus on technical and business capacities. Nonetheless, the initiative faced limitations, including a restricted number of respondents and a short implementation period, indicating the need for longitudinal evaluations to assess the sustainability of these initial changes.